ΤΟ ΕΠΑΓΓΕΛΜΑ ΤΟΥ ΣΥΜΒΟΛΑΙΟΓΡΑΦΟΥ ΣΤΗΝ ΚΕΡΚΥΡΑ ΕΠΙ ΒΕΝΕΤΟΚΡΑΤΙΑΣ - ΚΑΡΛΑΦΤΗ-ΜΟΥΡΑΤΙΔΗ, ΦΩΤΕΙΝΗ (Eoa kai Esperia, 2013)
The article discusses the legal status and the conditions to practise the profession of the notary, as well as the additional regulatory rules by the central and the local Venetian authorities. The notary is the representative of the written and the customary law, as he undertakes to inform the parties regarding their rights and their responsibilities, together with the penalties they are sentenced to in case of any violation of the agreed. The notary is the person who legalizes records and safeguards various economic and other activities. For these reasons, the successful choice of the persons that are going to practise the profession of the notary is crucial. The examination of the notaries’ qualifications is done by the local administration officials, who undertake to examine the knowledge and the skills of the candidate notaries, while great importance is given to the candidate’s way of life, their honesty and their morality in general, traits that are assured by their good reputation. Concerning those who already practise the profession, the main criterion for the continuance of the notary is the proper drafting and registration of the contracts in the notary record books based on the relevant regulations.